Peningkatan Hasil Belajar Melalui Model Pembelajaran Inkuiri Laboratorium pada Materi Asam, Basa, dan Garam di Sekolah Menengah Pertama - Syofia Yohana (Jurnal Pendidikan Biologi, 2018)
The problem faced in this study is the low science learning outcomes in material related to chemistry. The purpose of this study was to determine the improvement of student learning outcomes through the Laboratory Inquiry learning model on acid, alkaline, and salt material in class VII of SMP 1 Percut Sei Tuan Tahun. Action research was conducted in class VII of SMP Negeri 1 Percut Sei Tuan with a total of 32 students. The research took place in 2 cycles by expressing four stages in each cycle, namely: the stages of planning, implementation, observation, and reflection. Analysis of research data in the form of quantitative and qualitative data which is the student learning outcomes (pre-test and post-test) and the results of observations of students' skills utilizing percentage, namely by calculating the increase in student mastery learning individually. The results of the first cycle test, there were 17 students (53.13%) had achieved mastery learning while 15 students (46.87%) had not achieved mastery learning. After it was found that there was an increase, it continued to give action in the second cycle. Then the results of the second cycle test were found to have a substantial increase in the number of students completing, namely from 32 students. It turned out that 28 students (87.50%) had achieved mastery learning, only four students (12.50%) had not reached completeness in learning. Students' skills in conducting practicum have increased significantly. Based on the results of the first cycle test and the second cycle test, it can be concluded that the Laboratory Inquiry Learning Model on Acid, Base, and Salt material can improve the learning outcomes of junior high school students.